Enamel gloss changes induced by orthodontic bonding. (2nd October 2018) - Sifakakis, Iosif; Zinelis, Spiros; Eliades, George; Koletsi, Despina; Eliades, Theodore
ABSTRACT: Objective: The purpose of this study was to assess enamel gloss changes induced by orthodontic bracket bonding with a light-cured composite or a light-cured resin-reinforced glass ionomer cement. Setting: The Department of Biomaterials, School of Dentistry, National and Kapodistrian University of Athens, Greece. Design: Laboratory study. Methods: A total of twenty extracted upper human first premolars were included in this study and each tooth served as a control for itself. Their buccal surfaces were subjected to 60 o -angle gloss measurement (G%60) with a standardized and secure repeated analysis of the same site. After baseline evaluation, a bracket was bonded on the buccal surface of each tooth. Half of the specimens were bonded with acid-etching and a light-cured composite whereas the other half with a light-cured resin-reinforced glass ionomer cement without prior enamel conditioning. Gloss measurements were repeated after bracket debonding and removal of the composite/glass ionomer cement with an 18-fluted carbide bur. Gloss differences between the two measurement conditions (baseline and post-debonding) were analyzed through linear regression with standard errors derived using the bootstrap method. Level of significance was set at a < 0.05. Results: A statistically significant difference was detected between the tested groups for the outcome of interest. Teeth bonded with light-cured composite exhibited larger enamel gloss changes as compared to resin-reinforced glass ionomer cement ( β  = 0.74; 95% CIs: 0.10, 1.38; p  = 0.02). Conclusions: Bracket bonding with two common bonding protocols (acid-etching with a light-cured composite vs. no etching with resin reinforced glass-ionomer cement) and subsequently debonding and adhesive removal with an 18-fluted carbide bur induced enamel gloss changes.